A microscopic transungual surgical approach for subungual glomus tumor resection - Zhong, Jianbo; Ali, Kamran; Yang, Ping; Zhao, Xingyun; Xu Lou, Inmaculada; Wu, Liming (Frontiers in Medicine, 2025)
BackgroundGlomus tumors, rare benign neoplasms developing from the glomus, often pose challenges in early detection due to their small size and subtle symptoms. Surgical removal remains the only primary treatment; however, existing approaches have limitations, particularly in preserving nail structure and minimizing recurrence rates. This study introduces the Microscopic Transungual Surgical Approach to overcome the drawbacks of existing procedures for glomus tumor excision and evaluate its efficacy in treating these tumors.MethodsWe retrospectively analyzed 61 patients diagnosed with and treated for glomus tumors between 2014 and 2024, examining their clinical characteristics, diagnostic test results (Love’s and Hildreth’s tests), and MRI findings. The surgical approach included complete nail plate removal followed by microscopic tumor excision and attentive postoperative management.ResultsThe study included 61 glomus tumor patients [49 females (80.3%), 12 males (19.7%)] with a median age of 39 years. Tumors most commonly affected the thumb (39.3%) and ring finger (23.0%). Key clinical features included severe pain (98.4%), positive Love test (95.1%), and cold sensitivity (88.5%). Associated findings included nail deformities (50.8%) and bone changes (39.3%). At 1-year follow-up, 80.2% achieved satisfactory nail recovery, with a 4.9% recurrence rate.ConclusionOur study suggests the potential efficacy of the Microscopic Transungual Surgical Approach in treating glomus tumors. Its enhanced visualization contributes to complete removal of tumors with less surrounding tissue damage to lower recurrence rates and improved patient outcomes.